COMPLIANCE OFFICERS IN SERBIA: EMPLOYEES OR INTERIM MANAGERS? - Tošić, Iva; Miailović, Jovana (Pravni zapisi, 2023)
The first part of the paper analyzes the principle of legality in business and the basic features of the compliance function. Taking into account that the principle of legality in business is one of the core pillars for achieving good corporate governance, having a person who will perform the compliance function is of great significance. The legal position of the compliance officer may be differently regulated, whether as an employee or an outsourced expert. The second part of the paper deals with these two options taking into account the standing practice in the United Kingdom and Germany, where the compliance function has a long tradition. These examples may be challenging for Serbia to follow, since its compliance function is at the very beginning, although having a compliance officer (team) as an employee should be the ultimate objective. In the meantime, the authors propose for Serbian companies to hire compliance officers as interim managers as a solution.